Mouse Models to Study Dengue Virus Immunology and Pathogenesis - Zellweger, Raphaël M.; Shresta, Sujan (Frontiers in Immunology, 2014)
The development of a compelling murine model of dengue virus (DENV) infection has been challenging, because dengue virus clinical isolates do not readily replicate or cause pathology in immunocompetent mice. However, research using immunocompromised mice and/or mouse-adapted viruses allows to investigate questions that may be impossible to address in human studies. In this review, we discuss the potential strengths and limitations of existing mouse models of dengue disease. Human studies are descriptive by nature; moreover, the strain, time, and sequence of infection are often unknown. In contrast, in mice, the conditions of infection are well defined and a large number of experimental parameters can be varied at will. Therefore, mouse models offer an opportunity to experimentally test hypotheses that are based on epidemiological observations. In particular, gain-of-function or loss-of-function models can be established to assess how different components of the immune system (either alone or in combination) contribute to protection or pathogenesis during secondary infections or after vaccination. In addition, mouse models have been used for pre-clinical testing of antiviral drug or for vaccine development studies. Conclusions based on mouse experiments must be extrapolated to DENV infection in humans with caution due to the inherent limitations of animal models. However, research in mouse models is a useful complement to in vitro and epidemiological data, and may delineate new areas that deserve attention during future human studies.